Sensorimotor gating, working and social memory deficits in mice with reduced expression of the vesicular glutamate transporter VGLUT1 - Inta, Dragos; Schneider, Miriam; Spanagel, Rainer; Gass, Peter (Behavioural brain research, 2012)
Glutamate is the main excitatory neurotransmitter in the central nervous system. A hypoglutamatergic state is believed to play an important role in the pathophysiology of schizophrenia. The release of glutamate in the brain is modulated by a class of vesicular glutamate transporters, VGLUT1-3. Among them, VGLUT1 represents the isoform predominantly expressed in the neocortex and hippocampus. Here we investigated the potential involvement of VGLUT1 deficiency in generating schizophrenia-like abnormalities by testing mice with diminished expression of VGLUT1 in several behavioural tests relevant for schizophrenia. We found behavioural alterations in these mice resembling correlates of schizophrenia, such as working- and social memory impairments and deficits in prepulse inhibition (PPI) of the acoustic startle reflex (ASR), but normal locomotor behaviour under basal conditions. Our data may be important for a better understanding of the contribution of reduced VGLUT1-mediated presynaptic glutamatergic neurotransmission in the generation of several behavioural abnormalities associated with schizophrenia.